PMO-058 A simple and an effective strategy for improving juniors doctors' knowledge of intravenous fluid therapy. (28th May 2012) - Swayamprakasam, A P; Bijoor, P; Khalid, U; Rana, M S; Boulton, R; Taylor, A
Abstract : Introduction: Erroneous intravenous fluid therapy is a source of perioperative morbidity and mortality. 1 In most surgical units, junior doctors are given the major responsibility for prescribing intravenous fluids, even though their knowledge base is inadequate. 2–4 Training junior doctors in intravenous fluid therapy is required to improve their knowledge and reduce the harm caused by erroneous intravenous fluid therapy. In this study we evaluated whether a single focused teaching session, based on the current national guidelines for perioperative fluid therapy, could improve junior doctors' knowledge of intravenous fluid therapy. Methods: Junior doctors attended a focused teaching session on a perioperative fluid therapy. They completed the questionnaire at baseline, immediately after and again 2–5 weeks after the teaching session. The questionnaire was developed from the current national guidelines on perioperative intravenous fluid therapy; 2008 British Consensus Guidelines on Intravenous Fluid Therapy for Adult Surgical Patients. Results: The mean pre-education score was 4.3 (36%). The mean post-education scores immediately after and an average of 22 days after the teaching session were; 10.3 (85%) and 9.5 (79%) respectively. Conclusion: A single focused teaching session is a simple and an effective way of improving junior doctors' knowledge of intravenous fluid therapy. We recommend that a teaching session on intravenous fluids be integrated into the teaching programme of all junior doctors. Competing interests: None declared. References: 1. Callum KG, Gray AJG, Hoile RW, et al. Extremes of Age: The 1999 Report of the National Confidential Enquiry into Perioperative Deaths . London: National Confidential Enquiry into Perioperative Deaths, 1999. 2. Lobo DN, Dube MG, Neal KR, et al. Problems with solutions: drowning in the brine of an inadequate knowledge base. Clin Nutr 2001;20 :125–30. 3. Lobo DN, Dube MG, Neal KR, et al. Peri-operative fluid and electrolyte management: a survey of consultant surgeons in the UK. Ann R Coll Surg Engl 2002;84 :156–60. 4. Walsh SR, Walsh CJ. Intravenous fluid-associated morbidity in postoperative patients. Ann R Coll Surg Engl 2005;87 :126–30.